Wettability-adjustable Janus structure photo-thermal fabric as well as preparation method and application thereof
By using Janus structured photothermal fabric with adjustable wettability in solar-driven interface evaporation technology, the problem of light absorption and water evaporation coexisting on the same surface is solved, and water-energy balance and high efficiency are achieved Evaporation improves the stability and efficiency of the evaporator.
Patent Information
- Application Number
- CN202411424616.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-12
AI Technical Summary
In the existing solar-driven interface evaporation technology, light absorption and water evaporation coexist on the same surface, resulting in performance damage, and the supply and demand relationship of the evaporation process cannot be fully considered, resulting in heat loss and salt deposition problems, affecting long-term stability.
Using Janus structured photothermal fabric with adjustable wettability, the water content and transmission rate are regulated by forming a hydrophilic layer and a hydrophobic layer on the hydrophobic carbon fiber fabric, and the radial channel formed by CuS nanosheets are separated to separate the light absorption and water evaporation, and the water content and transmission rate are regulated. Achieve water-energy balance.
It improves the efficient long-term stability of the evaporator, reduces heat loss, prevents salt deposition, enhances thermal positioning and salt discharge rate, and improves the evaporation rate and salt resistance of the equipment.
Smart Images

Figure CN119145215A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar interface water evaporation, and in particular relates to a Janus structure photothermal fabric with adjustable wettability, and a preparation method and application thereof. Background Art
[0002] Obtaining fresh water from non-drinking water such as seawater or sewage is an effective way to alleviate the problem of fresh water shortage. To this end, many researchers have tried various methods, including reverse osmosis, electro-osmosis, and thermal distillation. However, these technologies require the consumption of a large amount of fossil fuels, which inevitably have an impact on the environment and require huge economic costs, which is not conducive to sustainable development. Inspired by natural evaporation, solar-driven evaporation using renewable solar energy as the only energy input to obtain fresh water has been considered a promising and sustainable solution. In particular, solar-driven interfacial evaporation (SDIE) has become a cost-effective fresh water production technology. This technology captures incident sunlight through a solar absorber and converts the light into localized thermal energy, which is confined at the water / air interface and evaporates water at the interface. This technology requires the coordination of solar absorbers, heat positioning, and water supply components.
[0003] As a kind of carbon-based material, carbon fiber fabric is considered to be an ideal photothermal material due to its inherent broadband absorption characteristics, low cost, easy structural control, and low environmental harm. When super-hydrophilic carbon fiber cloth fabric is used as a photothermal evaporator, it can achieve high light absorption rate and fast water transmission at the same time. However, since solar light absorption, water transmission and steam escape coexist on the same surface, they will inevitably affect each other, resulting in impaired performance. At the same time, the current SDIE system does not fully consider the supply and demand relationship of the evaporation process, which leads to excessive water supply causing huge heat loss, and too little water supply will cause salt deposition on the evaporation surface, blocking the evaporator, affecting the light absorption performance and continuous water supply as well as the long-term stability of the evaporator.
[0004] Therefore, it is particularly important to separate light absorption and water evaporation by preparing a wettable surface and to regulate the water content of the hydrophilic layer to establish a long-term stable water-energy balance during the evaporation process. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a Janus structure photothermal fabric with adjustable wettability and a preparation method and application thereof, so as to solve the problems of heat loss caused by water energy imbalance in the existing two-dimensional evaporator during evaporation, salt deposition on the evaporator surface, and eliminate the inevitable mutual influence caused by the coexistence of light absorption and water transmission of the evaporator in the same space, thereby improving the high efficiency and long-term stability of the evaporator.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a Janus structure photothermal fabric with adjustable wettability. The Janus structure photothermal fabric with adjustable wettability uses a hydrophobic carbon fiber fabric as a substrate, one side of the hydrophobic carbon fiber fabric is a hydrophilic layer, and the other side is a hydrophobic layer, the hydrophilic layer is a deposited CuS layer, and the hydrophobic layer is an undeposited CuS layer.
[0007] In one embodiment, the hydrophilic layer is a hydrophilic layer with radial pores formed by interlacing and connecting CuS nanosheets grown on the surface of the hydrophobic carbon fiber fabric.
[0008] The present invention also provides a method for preparing a Janus structure photothermal fabric with adjustable wettability, comprising the following steps: After being cleaned, the hydrophobic carbon fiber fabric is placed in a magnetron sputtering system, and argon gas is used as a sputtering gas to remove impurities on the surface of the hydrophobic carbon fiber fabric to obtain a clean hydrophobic carbon fiber fabric; a pre-sputtering treatment is performed on the Cu target to remove the oxide layer on the copper surface to obtain a Cu target without a surface oxide layer; A Cu target is sputtered on the surface of a clean hydrophobic carbon fiber fabric by a direct current power supply to obtain a hydrophobic carbon fiber fabric with a Cu layer deposited on one side; polyethylene glycol and deionized water are used as solvents, sodium hydroxide and sulfur powder are dissolved in the solvent to obtain a yellow mixed solution; The hydrophobic carbon fiber fabric with a Cu layer deposited on one side was immersed in a yellow mixed solution, and the copper sulfide layer was grown by reaction, then rinsed and dried to obtain a Janus structure photothermal fabric with controllable wettability.
[0009] In one embodiment, the process of using argon as a sputtering gas to remove impurities on the surface of the hydrophobic carbon fiber fabric is as follows: The high vacuum state in the chamber is 1.8×10 -3 Pa, 50 sccm of argon was introduced, the pressure was increased to 6 Pa, a bias of 400 V was applied, and the bombardment was carried out for 5-10 min.
[0010] In one embodiment, the pre-sputtering treatment is performed under a vacuum degree of 0.6 Pa, the pre-sputtering power value is 80-100 W, and the pre-sputtering time is 5-10 min.
[0011] In one embodiment, the current when sputtering the Cu target by a DC power supply is 0.3 A, the sputtering power is 80-100 W, the rotation speed of the clean hydrophobic carbon fiber fabric is 8-13 r / min, and after starting the power supply, the Cu target surface is glowed and discharged, and the sputtering time is 30-80 min.
[0012] In one embodiment, the mass ratio of the sodium hydroxide to the sulfur powder is 2-3:1; and the volume ratio of the polyethylene glycol to the deionized water is 1-2:15.
[0013] In one embodiment, the dissolving is carried out by stirring and dissolving at a temperature of 60-70° C., and the time of stirring and dissolving is 15-20 minutes; The temperature of the yellow mixed solution during the immersion is 20-25°C, and the reaction time is 2-3 minutes; the rinsing is carried out using propanol and deionized water, and the number of rinsing is 3-5 times; the drying temperature is 60-65°C, and the drying time is 3-3.5 hours.
[0014] In one embodiment, during the reaction growth of the copper sulfide layer, the color of the surface of the hydrophobic carbon fiber fabric with the Cu layer deposited on one side changes from copper color to black to generate a CuS layer to form a hydrophobic carbon fiber fabric with the CuS layer deposited on one side, and the surface wettability of the hydrophobic carbon fiber fabric changes from hydrophobic to hydrophilic.
[0015] The present invention also provides an application of the Janus structure photothermal fabric with adjustable wettability in a solar evaporator, wherein the solar evaporator comprises the Janus structure photothermal fabric with adjustable wettability, polystyrene foam and a dust-free cloth; the dust-free cloth wraps the polystyrene foam, and the hydrophilic layer of the Janus structure photothermal fabric with adjustable wettability is arranged on the polystyrene foam wrapped by the dust-free cloth.
[0016] Compared with the prior art, the present invention has the following beneficial effects: On the one hand, the present invention provides a Janus structure photothermal fabric with adjustable wettability, which is based on a hydrophobic carbon fiber fabric. The photothermal fabric includes a hydrophilic layer and a hydrophobic layer respectively located on the two surfaces of the Janus structure photothermal fabric, wherein the hydrophilic layer is a deposited CuS layer, and the hydrophobic layer is an undeposited CuS layer. The CuS nanosheets on the surface of the deposited CuS layer of the hydrophobic carbon fiber fabric are interlaced and connected to form abundant radial channels, which can be used as a bottom hydrophilic microchannel capillary water transport layer. The hydrophobic carbon fiber fabric without a copper coating, that is, the hydrophobic layer, serves as the top photothermal layer and still maintains hydrophobicity.
[0017] On the other hand, the present invention provides a method for preparing a Janus structure photothermal fabric with adjustable wettability, wherein a hydrophobic carbon fiber fabric is used as a substrate, a copper layer is deposited by magnetron sputtering to provide sites for subsequent chemical reactions, and CuS nanosheets are further grown on its surface to form a hydrophilic layer.
[0018] Furthermore, by adjusting the copper plating time to adjust the thickness of the bottom hydrophilic layer, different pores are formed to control the water content and water transfer rate, so that the solar interface evaporator has different water supply rates. The wettability design is used to balance the water supply rate and heat transfer rate to achieve efficient water supply and effective thermal management.
[0019] The present invention also provides, on the one hand, the above-mentioned Janus structure photothermal fabric with adjustable wettability for application in a solar evaporator, which is composed of a top hydrophobic layer, a bottom hydrophilic layer, and a polystyrene foam hydrophilic channel wrapped with a dust-free cloth, and the bottom hydrophilic layer is located above the hydrophilic channel. The top hydrophobic layer can effectively prevent salt ions from entering the light absorption layer, and the radial hydrophilic channels formed by the bottom CuS nanosheets can enhance thermal positioning and accelerate the salt discharge rate. The polystyrene foam hydrophilic channel wrapped with a dust-free cloth is used to accelerate salt diffusion and reflux. By changing the wettability of the hydrophobic carbon fiber cloth, solar light absorption and water evaporation are separated, eliminating the functional interference of the two mutually destructive functions, and allowing the two to be adjusted separately. The Janus structure evaporator can ensure the high evaporation performance and long-term stability of the evaporator while preventing salt deposition. Compared with traditional solar evaporators, this evaporator limits the water transmission channel to the surface of the evaporator, while ensuring sufficient water supply, reducing the contact area between water and the photothermal layer, thereby reducing heat loss and increasing the evaporation rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A schematic diagram of a Janus structure photothermal fabric with adjustable wettability provided by the present invention being applied to a solar evaporator; Figure 2 Figures a and b in the middle are SEM images of the bottom hydrophilic layer of the Janus structure photothermal fabric with adjustable wettability obtained in Example 1 of the present invention. Figure 2 Figures c and d in the middle are SEM images of the hydrophobic layer on the top surface of the Janus structure photothermal fabric with adjustable wettability in the present invention; Figure 3 It is a schematic diagram of the evaporation rate of the Janus structure photothermal fabric with adjustable wettability prepared in Example 1 of the present invention in salt water and the evaporation rate of pure salt water; Figure 4 This is a test diagram of the water contact angle of the hydrophilic layer of the Janus structure photothermal fabric with adjustable wettability obtained in Examples 1 to 4 of the present invention; Figure 5 This is a schematic diagram of the surface salt deposition of the Janus structure photothermal fabric evaporator with adjustable wettability prepared in Example 7 of the present invention during continuous evaporation in high-concentration salt water for 7 hours. DETAILED DESCRIPTION
[0021] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0022] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0023] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0024] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0025] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0026] The invention provides a Janus structure photothermal fabric with adjustable wettability, and a preparation method and application thereof.
[0027] On the one hand, the present invention provides a Janus structure photothermal fabric with adjustable wettability. The Janus structure photothermal fabric with adjustable wettability is based on a hydrophobic carbon fiber fabric, one side of the hydrophobic carbon fiber fabric is a hydrophilic layer, and the other side is a hydrophobic layer, the hydrophilic layer is a deposited CuS layer, and the hydrophobic layer is an undeposited CuS layer.
[0028] Specifically, the wettability-adjustable Janus structure photothermal fabric is constructed based on a hydrophobic carbon fiber fabric, and its two sides are designed as a hydrophilic layer and a hydrophobic layer respectively. The hydrophilic layer is realized by depositing CuS, while the hydrophobic layer maintains the original state of the carbon fiber without CuS deposition. The hydrophilic layer is a hydrophilic layer with radial pores formed by the interlaced connection between the CuS nanosheets grown on the surface of the hydrophobic carbon fiber fabric.
[0029] The hydrophilic layer is composed of CuS nanosheets grown on the surface of the hydrophobic carbon fiber fabric, which are interlaced and connected with each other. Abundant radial pores are formed between these nanosheets, forming a hydrophilic layer with a microchannel structure, which promotes the transport of water by capillary action.
[0030] On the other hand, the present invention discloses a method for preparing a Janus structure photothermal fabric with adjustable wettability, S1: the hydrophobic carbon fiber fabric is placed in a magnetron sputtering system after being cleaned, and argon is used as a sputtering gas to remove impurities on the surface of the hydrophobic carbon fiber fabric to obtain a clean hydrophobic carbon fiber fabric; for a Cu target, a pre-sputtering treatment is performed to remove the oxide layer on the copper surface to obtain a Cu target without a surface oxide layer.
[0031] S2: A Cu target is sputtered on the surface of a clean hydrophobic carbon fiber fabric by a DC power supply to obtain a hydrophobic carbon fiber fabric with a single-sided Cu layer deposited thereon; polyethylene glycol and deionized water are used as solvents, sodium hydroxide and sulfur powder are dissolved in the solvent to obtain a yellow mixed solution.
[0032] S3: The hydrophobic carbon fiber fabric with a single-sided Cu layer is immersed in a yellow mixed solution, and a copper sulfide layer is grown by reaction, then rinsed and dried to obtain a Janus structure photothermal fabric with adjustable wettability.
[0033] In one embodiment, argon is used as a sputtering gas to remove impurities on the surface of the hydrophobic carbon fiber fabric. -3 Pa, introduce 50 sccm argon gas and bombard for 5-10 min; the bias voltage is 400 V and the gas pressure is 6 Pa.
[0034] In one implementation process, a Cu target with a purity of 99.99% is pre-sputtered to remove the oxide layer on the copper surface; under a vacuum degree of 0.6 Pa, the pre-sputtering power value is 80-100 W, and the pre-sputtering time is 5-10 min.
[0035] In one implementation process, a DC power supply is used to sputter a Cu target, the current is 0.3 A, the sputtering power is 80-100 W, the rotation speed of the clean hydrophobic carbon fiber fabric is 8-13 r / min, and after starting the power supply, a glow discharge occurs on the surface of the Cu target, and the sputtering time is 30-80 min.
[0036] In one implementation process, the mass ratio of sodium hydroxide to sulfur powder is 2-3:1, and the volume ratio of polyethylene glycol to deionized water is 1-2:15; specifically, 600 mg of sodium hydroxide particles, 200 mg or 300 mg of sulfur powder, 1 mL or 2 mL of polyethylene glycol are weighed, 15 mL of deionized water is added, and heated and stirred at 60-70°C for 15-20 minutes to obtain a yellow mixed solution, in which a sodium sulfide solution exists.
[0037] In one implementation process, the yellow mixed solution is cooled to 20-25° C., the hydrophobic carbon fiber fabric with a single-sided Cu layer is immersed in the solution, reacted for 2-3 minutes, rinsed with propanol and deionized water for 3-5 times, and dried at 60-65° C. for 3-3.5 hours.
[0038] During the reaction growth of the copper sulfide layer, the color of the surface of the hydrophobic carbon fiber fabric with the Cu layer deposited on one side changes from copper to black to generate a CuS layer, forming a hydrophobic carbon fiber fabric with the CuS layer deposited on one side, and the surface wettability of the hydrophobic carbon fiber fabric changes from hydrophobic to hydrophilic.
[0039] Specifically, the following steps are included: 1. Cleaning the hydrophobic carbon fiber fabric substrate First, cut the hydrophobic carbon fiber fabric into the required size (e.g., 3×3 cm), then rinse the surface with ethanol and deionized water 3-5 times, and use an ear suction bulb to blow away the dust on the fabric surface.
[0040] 2. CB / CC@Cu obtained by magnetron sputtering copper plating The bottom surface of the hydrophobic carbon fiber fabric was copper plated using a magnetron sputtering device. The fabric was fixed to the sample stage at the top of the chamber, and the copper target was installed. The chamber was evacuated using a mechanical pump and a molecular pump, and the vacuum degree reached 1.8×10 -3 Pa, set the rotation speed of the sample stage to 8-13 r / min, and then introduce argon as the sputtering gas with a flux of 50 sccm. Bombard for 5-10 min in Ar plasma atmosphere to remove impurities on the hydrophobic carbon fiber fabric and improve the bonding strength between the coating and the fabric. The bias voltage is set to 400 V and the gas pressure is set to 6 Pa.
[0041] Subsequently, the vacuum pressure was further adjusted to 0.6 Pa, and the pre-sputtering power value was set to 80-100 W. Under this condition, the Cu target with a purity of 99.99% was pre-sputtered for 5-10 min to remove the oxide layer on the copper surface and improve the purity of the coating.
[0042] Finally, the baffle was opened, and the Cu target surface was discharged under a DC power supply with a current of 0.3 A, and the sputtered particles were deposited onto the surface of the hydrophobic carbon fiber fabric substrate under the action of the electric field. The sputtering power was 80-100 W, and the sputtering time was 30-80 min.
[0043] After the above steps, the CB / CC@Cu photothermal fabric with a single-sided copper layer was obtained.
[0044] 3. Preparation of CB / CC@CuS photothermal fabrics with adjustable wettability by chemical reaction First, 600 mg of sodium hydroxide particles and 300 mg or 200 mg of sulfur powder were added to 1 mL or 2 mL of polyethylene glycol, and then 15 mL of deionized water was added, and magnetic stirring was performed at 60-70 °C for 15-20 min to obtain a yellow mixed solution.
[0045] Secondly, when the mixed solution is cooled to 20-25 ℃, the CB / CC@Cu carbon fiber photothermal fabric with a single-sided Cu layer is impregnated for 2-3 minutes. The Cu surface turns black and generates CuS to obtain the CB / CC@CuS photothermal fabric (CCS).
[0046] Finally, the CB / CC@CuS photothermal fabric was washed with deionized water and propanol for 3-5 times, and dried at 60-65°C for 3-3.5h to obtain the CB / CC@CuS photothermal fabric with controllable wettability. One surface CB of the photothermal fabric was a hydrophobic surface, and the other surface CC@CuS was a hydrophilic surface.
[0047] On the one hand, the present invention provides a solar evaporator. The solar evaporator is prepared by using a Janus structure photothermal fabric with adjustable wettability, including the Janus structure photothermal fabric with adjustable wettability, polystyrene foam and a dust-free cloth; the dust-free cloth wraps the polystyrene foam, and the hydrophilic layer of the Janus structure photothermal fabric with adjustable wettability is arranged on the polystyrene foam wrapped by the dust-free cloth.
[0048] The specific process of preparing a solar evaporator using a Janus structure photothermal fabric with adjustable wettability is as follows: The polystyrene foam was cut into a circle with a diameter of 5 cm and wrapped with a dust-free cloth. The obtained CB / CC@CuS photothermal fabric with adjustable wettability was placed on the dust-free cloth, with the hydrophilic layer at the bottom and the hydrophobic layer at the top.
[0049] In the above preparation process, hydrophobic carbon fiber fabric is used as the substrate, and a copper layer is deposited by magnetron sputtering to provide sites for subsequent chemical reactions. By configuring a yellow mixed solution, CuS nanosheets are further grown on its surface. The nanosheets on the surface of the hydrophobic carbon fiber fabric are intertwined and connected to form abundant radial channels, which can be used as the bottom hydrophilic microchannel capillary water transport layer. The carbon fiber fabric without a copper layer is used as the top photothermal layer and still maintains hydrophobicity. Compared with traditional solar evaporators, this evaporator limits the water transmission channel to the surface of the evaporator, which reduces the contact area between water and the photothermal layer while ensuring sufficient water supply, thereby reducing heat loss and increasing the evaporation rate.
[0050] Janus structure photothermal fabric with adjustable wettability is applied in solar evaporator. Hydrophobic carbon fiber fabric is used as substrate, and a hydrophilic layer is grown on its surface. By adjusting the thickness of the bottom hydrophilic layer and forming different pores to control the water content and water transfer rate, the solar interface evaporator has different water supply rates. The wettability design is used to balance the water supply rate and heat transfer rate to achieve efficient water supply and effective thermal management. The evaporator consists of a top hydrophobic layer, a bottom hydrophilic layer, and a polystyrene foam hydrophilic channel wrapped with a dust-free cloth. The top hydrophobic layer can effectively prevent salt ions from entering the light absorption layer. The radial hydrophilic channels formed by the bottom CuS nanosheets can enhance thermal positioning and accelerate the salt discharge rate. The polystyrene foam hydrophilic channel wrapped with a dust-free cloth is used to accelerate salt diffusion and reflux. The Janus structure evaporator can prevent salt deposition while ensuring the high evaporation performance and long-term stability of the evaporator.
[0051] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0052] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0053] Embodiment 1: 1. Cleaning the carbon fiber fabric substrate First, the carbon fiber fabric was cut into the required size (e.g., 3×3 cm), and then the surface was rinsed with ethanol and deionized water for 3 times, and the dust on the fabric surface was blown away with an ear suction bulb.
[0054] 2. CB / CC@Cu obtained by magnetron sputtering copper plating The magnetron sputtering equipment was used to plate copper on the bottom surface of the carbon fiber fabric. The fabric was fixed to the sample stage at the top of the chamber, and the copper target was installed. The chamber was evacuated using a mechanical pump and a molecular pump, and the vacuum degree reached 1.8×10 -3 Pa, the rotation speed of the sample stage was set to 13 r / min, and then argon was introduced as the sputtering gas with a flux of 50 sccm. Impurities on the carbon fiber fabric were removed by bombardment for 10 min in an Ar plasma atmosphere to improve the bonding strength between the coating and the fabric. The bias voltage was set to 400 V and the gas pressure was set to 6 Pa.
[0055] Subsequently, the vacuum pressure was further adjusted to 0.6 Pa, and the pre-sputtering power value was set to 100 W. Under this condition, the Cu target with a purity of 99.99% was pre-sputtered for 5 min to remove the oxide layer on the copper surface and improve the purity of the coating.
[0056] Finally, the shutter was opened, and the Cu target surface was discharged under a DC power supply with a current of 0.3 A, and the sputtered particles were deposited on the substrate surface under the action of the electric field. The sputtering power was 100 W and the sputtering time was 30 min.
[0057] After the above steps, the CB / CC@Cu photothermal fabric with a single-sided copper layer was obtained.
[0058] 3. Preparation of CB / CC@CuS photothermal fabrics with adjustable wettability by chemical reaction First, 600 mg of sodium hydroxide particles and 300 mg of sulfur powder were added to 1 mL of polyethylene glycol, and then 15 mL of deionized water was added. The mixture was magnetically stirred at 60 °C for 20 min to obtain a yellow mixed solution.
[0059] Secondly, when the mixed solution was cooled to 20 ℃, the CB / CC@Cu carbon fiber photothermal fabric with a single-sided Cu layer was impregnated for 2 min, and the Cu surface turned black to obtain the CB / CC@CuS photothermal fabric (CCS).
[0060] Finally, the CB / CC@CuS photothermal fabric was washed with deionized water and propanol three times and dried at 60 °C for 3 h to obtain the CB / CC@CuS photothermal fabric with controllable wettability. The upper surface CB of the photothermal fabric was a hydrophobic layer, and the lower surface CC@CuS was a hydrophilic layer.
[0061] This embodiment also provides a solar evaporator using the Janus structure photothermal fabric with adjustable wettability, the solar evaporator comprising the Janus structure photothermal fabric with adjustable wettability, polystyrene foam and dust-free cloth; The polystyrene foam was cut into a circle with a diameter of 5 cm, wrapped with a dust-free cloth, and the obtained CB / CC@CuS photothermal fabric with adjustable wettability was placed on the dust-free cloth.
[0062] Embodiment 2: 1. Cleaning the carbon fiber fabric substrate First, the carbon fiber fabric was cut into the required size (e.g., 3×3 cm), and then the surface was rinsed with ethanol and deionized water for 5 times, and the dust on the fabric surface was blown away with an ear suction bulb.
[0063] 2. CB / CC@Cu obtained by magnetron sputtering copper plating The magnetron sputtering equipment was used to plate copper on the bottom surface of the carbon fiber fabric. The fabric was fixed to the sample stage at the top of the chamber, and the copper target was installed. The chamber was evacuated using a mechanical pump and a molecular pump, and the vacuum degree reached 1.8×10 -3 Pa, the rotation speed of the sample stage was set to 13 r / min, and then argon was introduced as the sputtering gas with a flux of 50 sccm. Impurities on the carbon fiber fabric were removed by bombardment for 10 min in an Ar plasma atmosphere to improve the bonding strength between the coating and the fabric. The bias voltage was set to 400 V and the gas pressure was set to 6 Pa.
[0064] Subsequently, the vacuum pressure was further adjusted to 0.6 Pa, and the pre-sputtering power value was set to 90 W. Under this condition, the Cu target with a purity of 99.99% was pre-sputtered for 5 min to remove the oxide layer on the copper surface and improve the purity of the coating.
[0065] Finally, the shutter was opened, and the Cu target surface was discharged under a DC power supply with a current of 0.3 A, and the sputtered particles were deposited on the substrate surface under the action of the electric field. The sputtering power was 90 W and the sputtering time was 50 min.
[0066] After the above steps, the CB / CC@Cu photothermal fabric with a single-sided copper layer was obtained.
[0067] 3. Preparation of CB / CC@CuS photothermal fabrics with adjustable wettability by chemical reaction First, 600 mg of sodium hydroxide particles and 300 mg of sulfur powder were added to 1 mL of polyethylene glycol, and then 15 mL of deionized water was added. The mixture was magnetically stirred at 60 °C for 20 min to obtain a yellow mixed solution.
[0068] Secondly, when the mixed solution was cooled to 20 ℃, the CB / CC@Cu carbon fiber photothermal fabric with a single-sided Cu layer was impregnated for 2 min, and the Cu surface turned black to obtain the CB / CC@CuS photothermal fabric (CCS).
[0069] Finally, the CB / CC@CuS photothermal fabric was washed with deionized water and propanol for 5 times and dried at 60 °C for 3 h to obtain the CB / CC@CuS photothermal fabric with controllable wettability. The upper surface CB of the photothermal fabric was a hydrophobic layer, and the lower surface CC@CuS was a hydrophilic layer.
[0070] This embodiment also provides a solar evaporator using the Janus structure photothermal fabric with adjustable wettability, the solar evaporator comprising the Janus structure photothermal fabric with adjustable wettability, polystyrene foam and dust-free cloth; The polystyrene foam was cut into a circle with a diameter of 5 cm, wrapped with a dust-free cloth, and the obtained CB / CC@CuS photothermal fabric with adjustable wettability was placed on the dust-free cloth.
[0071] Embodiment 3: 1. Cleaning the carbon fiber fabric substrate First, the carbon fiber fabric was cut into the required size (e.g., 3×3 cm), and then the surface was rinsed with ethanol and deionized water for 4 times, and the dust on the fabric surface was blown away with an ear suction bulb.
[0072] 2. CB / CC@Cu obtained by magnetron sputtering copper plating The magnetron sputtering equipment was used to plate copper on the bottom surface of the carbon fiber fabric. The fabric was fixed to the sample stage at the top of the chamber, and the copper target was installed. The chamber was evacuated using a mechanical pump and a molecular pump, and the vacuum degree reached 1.8×10 -3 Pa, the rotation speed of the sample stage was set to 13 r / min, and then argon was introduced as the sputtering gas with a flux of 50 sccm. Impurities on the carbon fiber fabric were removed by bombardment for 10 min in an Ar plasma atmosphere to improve the bonding strength between the coating and the fabric. The bias voltage was set to 400 V and the gas pressure was set to 6 Pa.
[0073] Subsequently, the vacuum pressure was further adjusted to 0.6 Pa, and the pre-sputtering power was set to 80 W. Under this condition, the Cu target with a purity of 99.99% was pre-sputtered for 10 min to remove the oxide layer on the copper surface and improve the purity of the coating.
[0074] Finally, the shutter was opened, and the Cu target surface was discharged under a DC power supply with a current of 0.3 A, and the sputtered particles were deposited on the substrate surface under the action of the electric field. The sputtering power was 80 W and the sputtering time was 70 min.
[0075] After the above steps, the CB / CC@Cu photothermal fabric with a single-sided copper layer was obtained.
[0076] 3. Preparation of CB / CC@CuS photothermal fabrics with adjustable wettability by chemical reaction First, 600 mg of sodium hydroxide particles and 300 mg of sulfur powder were added to 1 mL of polyethylene glycol, and then 15 mL of deionized water was added. The mixture was magnetically stirred at 70 °C for 20 min to obtain a yellow mixed solution.
[0077] Secondly, when the mixed solution was cooled to 25 ℃, the CB / CC@Cu carbon fiber photothermal fabric with a single-sided Cu layer was impregnated for 3 min, and the Cu surface turned black to obtain the CB / CC@CuS photothermal fabric (CCS).
[0078] Finally, the CB / CC@CuS photothermal fabric was washed with deionized water and propanol for 4 times and dried at 60 °C for 3 h to obtain the CB / CC@CuS photothermal fabric with controllable wettability. The upper surface CB of the photothermal fabric was a hydrophobic layer, and the lower surface CC@CuS was a hydrophilic layer.
[0079] This embodiment also provides a solar evaporator using the Janus structure photothermal fabric with adjustable wettability, the solar evaporator comprising the Janus structure photothermal fabric with adjustable wettability, polystyrene foam and dust-free cloth; The polystyrene foam was cut into a circle with a diameter of 5 cm, wrapped with a dust-free cloth, and the obtained CB / CC@CuS photothermal fabric with adjustable wettability was placed on the dust-free cloth.
[0080] Embodiment 4: 1. Cleaning the carbon fiber fabric substrate First, the carbon fiber fabric was cut into the required size (e.g., 3×3 cm), and then the surface was rinsed with ethanol and deionized water for 5 times, and the dust on the fabric surface was blown away with an ear suction bulb.
[0081] 2. CB / CC@Cu obtained by magnetron sputtering copper plating The magnetron sputtering equipment was used to plate copper on the bottom surface of the carbon fiber fabric. The fabric was fixed to the sample stage at the top of the chamber, and the copper target was installed. The chamber was evacuated using a mechanical pump and a molecular pump, and the vacuum degree reached 1.8×10 -3 Pa, the rotation speed of the sample stage was set to 13 r / min, and then argon was introduced as the sputtering gas with a flux of 50 sccm. Impurities on the carbon fiber fabric were removed by bombardment for 10 min in an Ar plasma atmosphere to improve the bonding strength between the coating and the fabric. The bias voltage was set to 400 V and the gas pressure was set to 6 Pa.
[0082] Subsequently, the vacuum pressure was further adjusted to 0.6 Pa, and the pre-sputtering power was set to 80 W. Under this condition, the Cu target with a purity of 99.99% was pre-sputtered for 10 min to remove the oxide layer on the copper surface and improve the purity of the coating.
[0083] Finally, the shutter was opened, and the Cu target surface was discharged under a DC power supply with a current of 0.3 A, and the sputtered particles were deposited on the substrate surface under the action of the electric field. The sputtering power was 80 W and the sputtering time was 80 min.
[0084] After the above steps, the CB / CC@Cu photothermal fabric with a single-sided copper layer was obtained.
[0085] 3. Preparation of CB / CC@CuS photothermal fabrics with adjustable wettability by chemical reaction First, 600 mg of sodium hydroxide particles and 300 mg of sulfur powder were added to 1 mL of polyethylene glycol, and then 15 mL of deionized water was added. The mixture was magnetically stirred at 70 °C for 20 min to obtain a yellow mixed solution.
[0086] Secondly, when the mixed solution was cooled to 25 ℃, the CB / CC@Cu carbon fiber photothermal fabric with a single-sided Cu layer was impregnated for 3 min, and the Cu surface turned black to obtain the CB / CC@CuS photothermal fabric (CCS).
[0087] Finally, the CB / CC@CuS photothermal fabric was washed with deionized water and propanol for 5 times and dried at 60 °C for 3 h to obtain the CB / CC@CuS photothermal fabric with controllable wettability. The upper surface CB of the photothermal fabric was a hydrophobic layer, and the lower surface CC@CuS was a hydrophilic layer.
[0088] This embodiment also provides a solar evaporator using the Janus structure photothermal fabric with adjustable wettability, the solar evaporator comprising the Janus structure photothermal fabric with adjustable wettability, polystyrene foam and dust-free cloth; The polystyrene foam was cut into a circle with a diameter of 5 cm, wrapped with a dust-free cloth, and the obtained CB / CC@CuS photothermal fabric with adjustable wettability was placed on the dust-free cloth.
[0089] Embodiment 5: 1. Cleaning the carbon fiber fabric substrate First, the carbon fiber fabric was cut into the required size (e.g., 3×3 cm), and then the surface was rinsed with ethanol and deionized water for 3 times, and the dust on the fabric surface was blown away with an ear suction bulb.
[0090] 2. CB / CC@Cu obtained by magnetron sputtering copper plating The magnetron sputtering equipment was used to plate copper on the bottom surface of the carbon fiber fabric. The fabric was fixed to the sample stage at the top of the chamber, and the copper target was installed. The chamber was evacuated using a mechanical pump and a molecular pump, and the vacuum degree reached 1.8×10 -3 Pa, the rotation speed of the sample stage was set to 13 r / min, and then argon was introduced as the sputtering gas with a flux of 50 sccm. Impurities on the carbon fiber fabric were removed by bombardment for 8 min in an Ar plasma atmosphere to improve the bonding strength between the coating and the fabric. The bias voltage was set to 400 V and the gas pressure was set to 6 Pa.
[0091] Subsequently, the vacuum pressure was further adjusted to 0.6 Pa, and the pre-sputtering power was set to 90 W. Under this condition, the Cu target with a purity of 99.99% was pre-sputtered for 8 min to remove the oxide layer on the copper surface and improve the purity of the coating.
[0092] Finally, the shutter was opened, and the Cu target surface was discharged under a DC power supply with a current of 0.3 A, and the sputtered particles were deposited on the substrate surface under the action of the electric field. The sputtering power was 90 W and the sputtering time was 60 min.
[0093] After the above steps, the CB / CC@Cu photothermal fabric with a single-sided copper layer was obtained.
[0094] 3. Preparation of CB / CC@CuS photothermal fabrics with adjustable wettability by chemical reaction First, 600 mg of sodium hydroxide particles and 300 mg of sulfur powder were added to 1 mL of polyethylene glycol, and then 15 mL of deionized water was added. The mixture was magnetically stirred at 70 °C for 20 min to obtain a yellow mixed solution.
[0095] Secondly, when the mixed solution was cooled to 25 ℃, the CB / CC@Cu carbon fiber photothermal fabric with a single-sided Cu layer was impregnated and reacted for 2 min, and the Cu surface turned black to obtain the CB / CC@CuS photothermal fabric (CCS).
[0096] Finally, the CB / CC@CuS photothermal fabric was washed with deionized water and propanol three times and dried at 60 °C for 3 h to obtain the CB / CC@CuS photothermal fabric with controllable wettability. The upper surface CB of the photothermal fabric was a hydrophobic layer, and the lower surface CC@CuS was a hydrophilic layer.
[0097] This embodiment also provides a solar evaporator using the Janus structure photothermal fabric with adjustable wettability, the solar evaporator comprising the Janus structure photothermal fabric with adjustable wettability, polystyrene foam and dust-free cloth; The polystyrene foam was cut into a circle with a diameter of 5 cm, wrapped with a dust-free cloth, and the obtained CB / CC@CuS photothermal fabric with adjustable wettability was placed on the dust-free cloth.
[0098] Embodiment 6: 1. Cleaning the carbon fiber fabric substrate First, the carbon fiber fabric was cut into the required size (e.g., 3×3 cm), and then the surface was rinsed with ethanol and deionized water for 4 times, and the dust on the fabric surface was blown away with an ear suction bulb.
[0099] 2. CB / CC@Cu obtained by magnetron sputtering copper plating The magnetron sputtering equipment was used to plate copper on the bottom surface of the carbon fiber fabric. The fabric was fixed to the sample stage at the top of the chamber, and the copper target was installed. The chamber was evacuated using a mechanical pump and a molecular pump, and the vacuum degree reached 1.8×10 -3Pa, the rotation speed of the sample stage was set to 13 r / min, and then argon was introduced as the sputtering gas with a flux of 50 sccm. Impurities on the carbon fiber fabric were removed by bombardment for 8 min in an Ar plasma atmosphere to improve the bonding strength between the coating and the fabric. The bias voltage was set to 400 V and the gas pressure was set to 6 Pa.
[0100] Subsequently, the vacuum pressure was further adjusted to 0.6 Pa, and the pre-sputtering power was set to 90 W. Under this condition, the Cu target with a purity of 99.99% was pre-sputtered for 8 min to remove the oxide layer on the copper surface and improve the purity of the coating.
[0101] Finally, the shutter was opened, and the Cu target surface was discharged under a DC power supply with a current of 0.3 A, and the sputtered particles were deposited on the substrate surface under the action of the electric field. The sputtering power was 90 W and the sputtering time was 40 min.
[0102] After the above steps, the CB / CC@Cu photothermal fabric with a single-sided copper layer was obtained.
[0103] 3. Preparation of CB / CC@CuS photothermal fabrics with adjustable wettability by chemical reaction First, 600 mg of sodium hydroxide particles and 300 mg of sulfur powder were added to 1 mL of polyethylene glycol, and then 15 mL of deionized water was added. The mixture was magnetically stirred at 60 °C for 20 min to obtain a yellow mixed solution.
[0104] Secondly, when the mixed solution was cooled to 20 ℃, the CB / CC@Cu carbon fiber photothermal fabric with a single-sided Cu layer was impregnated for 2 min, and the Cu surface turned black to obtain the CB / CC@CuS photothermal fabric (CCS).
[0105] Finally, the CB / CC@CuS photothermal fabric was washed with deionized water and propanol three times and dried at 60 °C for 3 h to obtain the CB / CC@CuS photothermal fabric with controllable wettability. The upper surface CB of the photothermal fabric was a hydrophobic layer, and the lower surface CC@CuS was a hydrophilic layer.
[0106] This embodiment also provides a solar evaporator using the Janus structure photothermal fabric with adjustable wettability, the solar evaporator comprising the Janus structure photothermal fabric with adjustable wettability, polystyrene foam and dust-free cloth; The polystyrene foam was cut into a circle with a diameter of 5 cm, wrapped with a dust-free cloth, and the obtained CB / CC@CuS photothermal fabric with adjustable wettability was placed on the dust-free cloth.
[0107] Embodiment 7: 1. Cleaning the carbon fiber fabric substrate First, the carbon fiber fabric was cut into the required size (e.g., 3×3 cm), and then the surface was rinsed with ethanol and deionized water for 3 times, and the dust on the fabric surface was blown away with an ear suction bulb.
[0108] 2. CB / CC@Cu obtained by magnetron sputtering copper plating The magnetron sputtering equipment was used to plate copper on the bottom surface of the carbon fiber fabric. The fabric was fixed to the sample stage at the top of the chamber, and the copper target was installed. The chamber was evacuated using a mechanical pump and a molecular pump, and the vacuum degree reached 1.8×10 -3 Pa, the rotation speed of the sample stage was set to 13 r / min, and then argon was introduced as the sputtering gas with a flux of 50 sccm. Impurities on the carbon fiber fabric were removed by bombardment for 5 min in an Ar plasma atmosphere to improve the bonding strength between the coating and the fabric. The bias voltage was set to 400 V and the gas pressure was set to 6 Pa.
[0109] Subsequently, the vacuum pressure was further adjusted to 0.6 Pa, and the pre-sputtering power value was set to 100 W. Under this condition, the Cu target with a purity of 99.99% was pre-sputtered for 5 min to remove the oxide layer on the copper surface and improve the purity of the coating.
[0110] Finally, the shutter was opened, and the Cu target surface was discharged under a DC power supply with a current of 0.3 A. The sputtered particles were deposited on the substrate surface under the action of the electric field. The sputtering power was 100 W and the sputtering time was 65 min.
[0111] After the above steps, the CB / CC@Cu photothermal fabric with a single-sided copper layer was obtained.
[0112] 3. Preparation of CB / CC@CuS photothermal fabrics with adjustable wettability by chemical reaction First, 600 mg of sodium hydroxide particles and 300 mg of sulfur powder were added to 1 mL of polyethylene glycol, and then 15 mL of deionized water was added. The mixture was magnetically stirred at 70 °C for 20 min to obtain a yellow mixed solution.
[0113] Secondly, when the mixed solution was cooled to 20 ℃, the CB / CC@Cu carbon fiber photothermal fabric with a single-sided Cu layer was impregnated for 3 min, and the Cu surface turned black to obtain the CB / CC@CuS photothermal fabric (CCS).
[0114] Finally, the CB / CC@CuS photothermal fabric was washed with deionized water and propanol for 5 times and dried at 60 °C for 3 h to obtain the CB / CC@CuS photothermal fabric with controllable wettability. The upper surface CB of the photothermal fabric was a hydrophobic layer, and the lower surface CC@CuS was a hydrophilic layer.
[0115] This embodiment also provides a solar evaporator using the Janus structure photothermal fabric with adjustable wettability, the solar evaporator comprising the Janus structure photothermal fabric with adjustable wettability, polystyrene foam and dust-free cloth; The polystyrene foam was cut into a circle with a diameter of 5 cm, wrapped with a dust-free cloth, and the obtained CB / CC@CuS photothermal fabric with adjustable wettability was placed on the dust-free cloth.
[0116] Embodiment 8: 1. Cleaning the carbon fiber fabric substrate First, the carbon fiber fabric was cut into the required size (e.g., 3×3 cm), and then the surface was rinsed with ethanol and deionized water for 3 times, and the dust on the fabric surface was blown away with an ear suction bulb.
[0117] 2. CB / CC@Cu obtained by magnetron sputtering copper plating The magnetron sputtering equipment was used to plate copper on the bottom surface of the carbon fiber fabric. The fabric was fixed to the sample stage at the top of the chamber, and the copper target was installed. The chamber was evacuated using a mechanical pump and a molecular pump, and the vacuum degree reached 1.8×10 -3 Pa, the rotation speed of the sample stage was set to 8 r / min, and then argon was introduced as the sputtering gas with a flux of 50 sccm. Impurities on the carbon fiber fabric were removed by bombardment for 5 min in an Ar plasma atmosphere to improve the bonding strength between the coating and the fabric. The bias voltage was set to 400 V and the gas pressure was set to 6 Pa.
[0118] Subsequently, the vacuum pressure was further adjusted to 0.6 Pa, and the pre-sputtering power value was set to 100 W. Under this condition, the Cu target with a purity of 99.99% was pre-sputtered for 10 minutes to remove the oxide layer on the copper surface and improve the purity of the coating.
[0119] Finally, the shutter was opened, and the Cu target surface was discharged under a DC power supply with a current of 0.3 A. The sputtered particles were deposited on the substrate surface under the action of the electric field. The sputtering power was 100 W and the sputtering time was 65 min.
[0120] After the above steps, the CB / CC@Cu photothermal fabric with a single-sided copper layer was obtained.
[0121] 3. Preparation of CB / CC@CuS photothermal fabrics with adjustable wettability by chemical reaction First, 600 mg of sodium hydroxide particles and 200 mg of sulfur powder were added to 2 mL of polyethylene glycol, and then 15 mL of deionized water was added. The mixture was magnetically stirred at 70 °C for 15 min to obtain a yellow mixed solution.
[0122] Secondly, when the mixed solution was cooled to 20 ℃, the CB / CC@Cu carbon fiber photothermal fabric with a single-sided Cu layer was impregnated for 3 min, and the Cu surface turned black to obtain the CB / CC@CuS photothermal fabric (CCS).
[0123] Finally, the CB / CC@CuS photothermal fabric was washed with deionized water and propanol for 5 times, and dried at 65°C for 3.5 h to obtain the CB / CC@CuS photothermal fabric with controllable wettability. The upper surface CB of the photothermal fabric was a hydrophobic layer, and the lower surface CC@CuS was a hydrophilic layer.
[0124] This embodiment also provides a solar evaporator using the Janus structure photothermal fabric with adjustable wettability, the solar evaporator comprising the Janus structure photothermal fabric with adjustable wettability, polystyrene foam and dust-free cloth; The polystyrene foam was cut into a circle with a diameter of 5 cm, wrapped with a dust-free cloth, and the obtained CB / CC@CuS photothermal fabric with adjustable wettability was placed on the dust-free cloth.
[0125] In order to eliminate the inevitable mutual influence caused by the coexistence of light absorption and water transmission in the same space in traditional super-hydrophilic evaporators, Figure 1 A schematic diagram of a Janus structure photothermal fabric with adjustable wettability applied to a solar evaporator is shown. The evaporator consists of a top hydrophobic layer, a bottom 2D water supply channel, and a hydrophilic layer formed by radial pores. The top hydrophobic layer can achieve efficient light absorption and salt blocking, the bottom water supply channel can enhance thermal positioning and speed up salt discharge, and the hydrophilic layer formed by radial pores is used to accelerate the diffusion and reflux of salt ions. By adjusting the thickness of the hydrophilic layer, the water content transported to the inside or surface of the photothermal material can be matched with the input energy, and the salt ion reflux in the hydrophilic layer of the Janus membrane can also be achieved, which can not only avoid solar energy being used to heat too much water, but also effectively prevent the negative impact of salt crystallization on the evaporator, thereby greatly improving the evaporation efficiency and long-term stability of the evaporator.
[0126] Figure 2 Figures a and b in the middle are SEM images of the hydrophilic layer on the bottom surface of the Janus structure photothermal fabric with adjustable wettability obtained in Example 1 of the present invention. Figure 2 c, d are SEM images of the hydrophobic layer on the top surface of the Janus structure photothermal fabric with adjustable wettability in the present invention. Figure 2 a is the original morphology of the hydrophobic carbon fiber fabric. The hydrophobic carbon fiber fabric is woven from criss-crossed carbon fibers with a smooth fiber surface. The CC / CuS hydrophilic layer is obtained through a series of physical and chemical reactions. Figure 2As shown in b, a large number of microscopic pore structures of different sizes can be observed inside. The existence of these radial micropore structures significantly increases the transmission speed of capillary water, which is beneficial to the transmission, diffusion and reflux of solutes. Figure 2 From c and d, it can be seen that the surface of the hydrophobic carbon fiber fabric contains a large amount of carbon black (CB) particles, which increases the specific surface area of the hydrophobic layer and thus improves the light absorption efficiency.
[0127] Figure 3 The figure is a schematic diagram of the evaporation rate of the Janus structure photothermal fabric with adjustable wettability obtained in Example 1 of the present invention in salt water and the evaporation rate of pure salt water. As can be seen from the figure, the Janus structure photothermal fabric with adjustable wettability as an evaporator has an evaporation rate of 1.97 kg·m for 3.5wt% NaCl solution under one sun irradiation. -2 ·h -1 , compared with pure salt water (0.84 kg·m -2 ·h -1 ) and untreated carbon fiber fabric (1.75 kg·m -2 ·h -1 ) were increased by 2.4 and 1.2 times, respectively, proving that the evaporator has good light-to-heat conversion performance and water transport performance.
[0128] Figure 4 The water contact angle test diagram of the hydrophilic layer of the Janus structure photothermal fabric with adjustable wettability obtained in Examples 1 to 4 of the present invention is shown. As can be seen from the figure, 50 μL of water droplets were dropped on the surface of the hydrophilic layer of the photothermal fabric with adjustable wettability obtained in Examples 1 to 4, and CCS-1, CCS-2, CCS-3 and CCS-4 were completely absorbed after 2920 ms, 2260 ms, 1880 ms and 410 ms, respectively, proving that the obtained Janus structure carbon fiber photothermal fabric has adjustable wettability.
[0129] Figure 5 The figure is a schematic diagram of the surface salt deposition of the Janus structure photothermal fabric evaporator with adjustable wettability prepared in Example 7 of the present invention in high-concentration salt water after continuous evaporation for 7 hours. As shown in the figure, under one solar intensity, the Janus structure photothermal fabric with adjustable wettability prepared in Example 7 is used as an evaporator. After continuous operation for 7 hours in a 25wt% NaCl solution, the evaporator still exhibits a stable evaporation rate, with only a small amount of salt crystallization appearing at the edge of the evaporator, and having no obvious effect on the light absorption and steam overflow of the evaporator, indicating that the evaporator has good salt resistance and long-term stability.
[0130] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A Janus structure photothermal fabric with adjustable wettability. It is characterized in that The wettability-adjustable Janus structure photothermal fabric is based on a hydrophobic carbon fiber fabric, one side of the hydrophobic carbon fiber fabric is a hydrophilic layer, and the other side is a hydrophobic layer, the hydrophilic layer is a deposited CuS layer, and the hydrophobic layer is an undeposited CuS layer.
2. The Janus structured photothermal fabric with adjustable wettability according to claim 1, It is characterized in that The hydrophilic layer is a hydrophilic layer with radial pores formed by interlacing and connecting CuS nanosheets grown on the surface of the hydrophobic carbon fiber fabric.
3. A method for preparing the Janus structure photothermal fabric with adjustable wettability according to any one of claims 1 to 2, It is characterized in that The following steps are involved: After being cleaned, the hydrophobic carbon fiber fabric is placed in a magnetron sputtering system, and argon gas is used as a sputtering gas to remove impurities on the surface of the hydrophobic carbon fiber fabric to obtain a clean hydrophobic carbon fiber fabric; a pre-sputtering treatment is performed on the Cu target to remove the oxide layer on the copper surface to obtain a Cu target without a surface oxide layer; A Cu target is sputtered on the surface of a clean hydrophobic carbon fiber fabric by a direct current power supply to obtain a hydrophobic carbon fiber fabric with a Cu layer deposited on one side; polyethylene glycol and deionized water are used as solvents, sodium hydroxide and sulfur powder are dissolved in the solvent to obtain a yellow mixed solution; The hydrophobic carbon fiber fabric with a Cu layer deposited on one side was immersed in a yellow mixed solution, and the copper sulfide layer was grown by reaction, then rinsed and dried to obtain a Janus structure photothermal fabric with controllable wettability.
4. The method for preparing the Janus structure photothermal fabric with adjustable wettability according to claim 3, It is characterized in that The process of using argon as a sputtering gas to remove impurities on the surface of the hydrophobic carbon fiber fabric is as follows: The high vacuum state in the chamber is 1.8×10 -3 Pa, 50 sccm of argon was introduced, the pressure was increased to 6 Pa, a bias of 400 V was applied, and the bombardment was carried out for 5-10 min.
5. The method for preparing the Janus structure photothermal fabric with adjustable wettability according to claim 3, It is characterized in that The pre-sputtering treatment is carried out under a vacuum degree of 0.6 Pa, the pre-sputtering power value is 80-100 W, and the pre-sputtering time is 5-10 min.
6. The method for preparing the Janus structure photothermal fabric with adjustable wettability according to claim 3, It is characterized in that The current when sputtering the Cu target through the DC power supply is 0.3 A, the sputtering power is 80-100 W, the rotation speed of the clean hydrophobic carbon fiber fabric is 8-13 r / min, and after starting the power supply, the Cu target surface is glowed and discharged, and the sputtering time is 30-80 minutes.
7. The method for preparing the Janus structure photothermal fabric with adjustable wettability according to claim 3, It is characterized in that The mass ratio of the sodium hydroxide to the sulfur powder is 2-3:1; the volume ratio of the polyethylene glycol to the deionized water is 1-2:
15.
8. The method for preparing the Janus structure photothermal fabric with adjustable wettability according to claim 3, It is characterized in that The dissolving is carried out by stirring and dissolving at a temperature of 60-70° C., and the time for stirring and dissolving is 15-20 minutes; The temperature of the yellow mixed solution during the immersion is 20-25°C, and the reaction time is 2-3 minutes; the rinsing is carried out using propanol and deionized water, and the number of rinsing is 3-5 times; the drying temperature is 60-65°C, and the drying time is 3-3.5 hours.
9. The method for preparing the Janus structure photothermal fabric with adjustable wettability according to claim 3, It is characterized in that During the reaction growth of the copper sulfide layer, the color of the surface of the hydrophobic carbon fiber fabric with the Cu layer deposited on one side changes from copper to black to generate a CuS layer, forming a hydrophobic carbon fiber fabric with the CuS layer deposited on one side, and the surface wettability of the hydrophobic carbon fiber fabric changes from hydrophobic to hydrophilic.
10. Application of the Janus structured photothermal fabric with adjustable wettability according to any one of claims 1 to 2 in a solar evaporator, It is characterized in that The solar evaporator comprises a Janus structure photothermal fabric with adjustable wettability, polystyrene foam and a dust-free cloth; the dust-free cloth wraps the polystyrene foam, and the hydrophilic layer of the Janus structure photothermal fabric with adjustable wettability is arranged on the polystyrene foam wrapped by the dust-free cloth.
Citation Information
Patent Citations
Method for preparing photothermal conversion textile
CN106958141A
Application of photothermal-conversion cupric sulfidecomposite film in water treatment
CN107235591A
Phototropic solar photo-thermal seawater evaporation method and phototropic solar photo-thermal seawater evaporation device
CN111348708A
Interface evaporation device with porous hydrophobic / hydrophilic structure and preparation method of interface evaporation device
CN115124101A
Liquid diode flexible evaporator based on copper hydroxide, preparation method and application
CN116904928A
Cited By
Ultrathin hydrophilic / hydrophobic ZnO-CuS-CC photo-thermal material as well as preparation method and application thereof
CN119680578A
An ultrathin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material, its preparation method and application
CN119680578B
Plane cocoon evaporator capable of realizing large-scale production of transverse layered Janus structure, method and application
CN121044669A
Large scale production of planar cocoon evaporators with laterally layered janus structures and methods and applications
CN121044669B
